2004
DOI: 10.1007/s11661-004-0104-x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-imaging technologies for detecting damage during high-cycle fatigue

Abstract: A high-speed and high-sensitivity thermographic-infrared (IR) imaging system has been used for nondestructive evaluation of specimen-temperature evolutions during high-cycle fatigue experiments. The relationship among the temperature, stress-strain state, and fatigue behavior is discussed. Both thermodynamics and heat-transfer theories are applied to model and quantify the observed temperature variations during fatigue. The predicted and measured temperature evolutions and inelastic strains during fatigue were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…The shear-band patterns on the surfaces of post-deformed specimens were observed, using SEM. A nondestructive-evaluation state-of-the-art Indigo Phoenix thermographic-infrared camera was employed to observe in situ the dynamic shear-banding operations on the surfaces of the specimens with square cross sections at a frame rate of 1000 Hz (Chen et al, 2004;Liaw et al, 2000;Jiang et al, 2001Jiang et al, , 2002Jiang et al, , 2004Wang et al, 2000Wang et al, , 2002Yang et al, 2001Yang et al, , 2004a. In order to reduce the surface-heat reflection, a thin sub-micron graphite coating was applied on the specimen's surface to be observed.…”
Section: Methodsmentioning
confidence: 99%
“…The shear-band patterns on the surfaces of post-deformed specimens were observed, using SEM. A nondestructive-evaluation state-of-the-art Indigo Phoenix thermographic-infrared camera was employed to observe in situ the dynamic shear-banding operations on the surfaces of the specimens with square cross sections at a frame rate of 1000 Hz (Chen et al, 2004;Liaw et al, 2000;Jiang et al, 2001Jiang et al, , 2002Jiang et al, , 2004Wang et al, 2000Wang et al, , 2002Yang et al, 2001Yang et al, , 2004a. In order to reduce the surface-heat reflection, a thin sub-micron graphite coating was applied on the specimen's surface to be observed.…”
Section: Methodsmentioning
confidence: 99%
“…Numerical simulation is a very good approach for this purpose. Jiang et al (10), (11) and Yang et al (12), (13) analyzed the temperature evolution during cyclic loading of Ultimet alloy by one-dimensional numerical simulation for some early cycles. However, to the authors' knowledge, there is no other researcher focuses on numerical simulation.…”
Section: Introductionmentioning
confidence: 99%
“…[19] and [20], it can be shown that [23] It can also be found from Eqs. [19] and [20] that the fatiguestrength coefficient, Ј f , and fatigue-ductility coefficient, Ј f , are related to the plastic-strain energy during cyclic fatigue, and materials constants as well.…”
Section: Total Plastic-strain-energy Density As a Criterion For Fmentioning
confidence: 86%
“…Since the increment of the mean temperature of the fatigue specimen was mainly due to the energy dissipation of the irreversible deformation, the dissipated energy could be equated to a constant heat source uniformly distributed in the gage section of the specimen [17][18][19][20][21][22][23][24][25][26] . Because the elastic stress did not contribute to the increment of the mean temperature, the elastic stress field in the specimen was neglected.…”
Section: Temperature As An Index For the Fatigue-life Prediction Omentioning
confidence: 99%